The Relationship between Childhood Abuse, Religiosity and Life Satisfaction. - Dodoo, N. (University of Ghana, 2014)
The study investigated the relationship between childhood abuse (psychological, physical, sexual, and neglect), religiosity and later life satisfaction among adults with history of childhood abuse in any form. One hundred and thirty three adults, with a history of childhood abuse were purposively sampled from Tema SOS Village. It is an institution that provides day care, education, medical, psycho-social support and vocational training for people who have suffered abuse. Participants completed questionnaires on their retrospective childhood abuse experiences, religiosity and current life satisfaction. MANOVA and regression analysis were run on the data. Results indicated that childhood abuse was higher among females compared to their male counterparts. No gender differences were however found with respect to religiosity and life satisfaction. Composite childhood abuse was found to significantly influence life satisfaction with perceived religiosity moderating the relationship. Gender and marital status were found not to moderate the relationship between life satisfaction and childhood abuse.
Thesis (MPhil) - University of Ghana, 2014